Survey the quality of nursing care delivery to hemodialysis patients and nurses, level of knowledge of peritoneal dialysis in hospitals affiliated to Tehran University of Medical Sciences - Marbaghi A; heroabadi Sh; seyed-; kamali P (Iran University of Medical Sciences, 1994)
This descriptive and analytical study was conducted to evaluate quality quality of nursing care by nurses in hemodialysis patients and Their knowledge of peritoneal dialysis in hospitals affiliated to Tehran University of Medical Sciences.   In this study , 40 nurses graduated with bachelor , master and associae degree were participated. Data gathering was accomplished by questionnaire consists of 9 items about assessment of knowledge of peritoneal dialysis and checklist contains 4 questions in relation to the quality of nursing care is taken in hemodialysis patients .   The findings have been developed in 34 tables and a chart. The Pearson,s correlation coefficient and chi-square test was used to determine nurses, level of knowledge of peritoneal dialysis and evaluating the quality of nursing care delivery to hemodialysis patients nursing and variables such as age , marital status, monthly income , work experience in nursing, work experience in dialysis unit and special courses in dialysis. Overall the resaerch results showed that the quality of nursing care provided to patient before, during and after dialysis is not of good quality.